Kamusi ya biashara na uchumi : Kiingereza-Kiswahili - Tumbo-Masabo, Zubeida Zuberi; Chuwa, A. R. (Dar es Salaam : Taasisi ya Uchunguzi wa Kiswahili, Chuo Kikuu cha Dar es Salaam, 1999)
An English Swahili dictionary of business and commerce.
In Swahili, with some English.
Keywords: Business -- Dictionaries -- English; Commerce -- Dictionaries -- English; English language -- Dictionaries -- Swahili